The Influence of Entrepreneurial Motivation, Innovation on Business Sustainability Moderated by Limited Resources in MSMEs in Bulukumba Regency - Aslinda Anwar; Ismail Rasulong; Muchriady Muchran; Dg Maklassa; Andi Mappatompo (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of entrepreneurial motivation and innovation on business sustainability and to examine the moderating role of limited resources in Micro, Small, and Medium Enterprises (MSMEs) in Bulukumba Regency. This research employs a quantitative approach by distributing questionnaires to MSME actors in Bulukumba Regency. The analysis focuses on the relationships between entrepreneurial motivation, innovation, and business sustainability, with limited resources tested as a moderating variable. The findings indicate that entrepreneurial motivation does not have a significant effect on business sustainability, suggesting that psychological motivation alone is insufficient without adequate technical and financial competencies. In contrast, innovation has a positive and significant effect on business sustainability, highlighting the importance of creativity and product adaptation in maintaining competitive advantage. Furthermore, the moderating analysis shows that limited resources do not moderate the relationship between entrepreneurial motivation and business sustainability. However, limited resources significantly weaken the influence of innovation on business sustainability, indicating that constraints in capital, technology, and human resources hinder the effectiveness of innovative strategies. These findings imply that strengthening innovation capabilities is essential for MSME sustainability. Therefore, MSME actors are encouraged to improve managerial literacy, optimize the use of digital technology, and enhance collaborative networks among business actors to overcome resource limitations and strengthen collective business resilience.